Concurrent incidence of noma and necrotizing fasciitis in a male child: A rare clinical case report from a referral hospital in Northwest Nigeria - Mujtaba Bala; Abubakar Abdullahi Bello; Ramat Oyebunmi Braimah; Abdurrazaq Olanrewaju Taiwo; Mohammed Adam Sheikh Abdullahi (Wolters Kluwer Medknow Publications, 2023)
Rationale: Noma and necrotizing fasciitis are rapidly destructive gangrenous infections with different patterns of spread. This study aimed to present a case of concurrently occurring noma and necrotizing fascitis in a 3-year-old child. Patient Concern: A 3-year-old child with a low socioeconomic background presented with a main complaint of a painful wound on the gum, upper lip, and chest region. Diagnosis: Thorough history and examination revealed simultaneously occurring noma lesion extending from the inner labial mucosa to the upper lip and NF on the chest region on background anemia and malnutrition. Intervention: The patient was successfully treated with antibiotics, serial wound debridement, and supportive therapy. Outcome: The length of hospital stay was 6 weeks and there was uneventful healing. The patient is being followed up for complete resolution. Lessons: In this study, noma and NF were found to occur concurrently in a patient with malnutrition and anemia and Klebsiella species were the isolates in both wounds and could have been the common causative agent for both.